'To build a generation of stars': Megachurch identity, religion and modernity in Indonesia. (December 2016) - Yip, Jeaney; Hoon, Chang-Yau
Against the backdrop of dominant Muslim presence, an aspiring middle class and the modernisation of Indonesia as an emerging market, we explore how a contemporary megachurch in Indonesia constructs a corporate identity and examine how 'Western' ideals and modernity influence organisational practices and communication in a religious setting. We deploy discourse analysis as our approach, which includes a critical reading and semiotic analysis of corporate artefacts to understand their underlying structures and discourse in enacting the corporate identity. We examine how discourses of self-empowerment, Westernisation and modernisation, business and nationalism coalesce to construct a marketable corporate identity for the megachurch. From this perspective, we argue that corporate identity is fluid and is shaped by meaningful choices taken to discursively construct a particular image for its intended audience(s).